2017
DOI: 10.1016/j.ejvs.2016.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Editor's Choice – Dual Antiplatelet Therapy Improves Outcome in Diabetic Patients Undergoing Endovascular Femoropopliteal Stenting for Critical Limb Ischaemia

Abstract: DAPT with aspirin and clopidogrel compared to aspirin alone was associated with a lower amputation rate but not a higher bleeding rate in patients with diabetes and CLI after endovascular femoropopliteal stenting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 29 publications
0
18
1
1
Order By: Relevance
“…The main finding is interesting for a number of reasons. Although the study had appropriate statistical power to detect differences similar to the previously published literature, the case mix is different with fewer diabetics in our study than one of the large cohort studies used for the calculation [7]. As event rates were higher in the diabetic cohort in this study it may be no effect is shown in our data as a result.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…The main finding is interesting for a number of reasons. Although the study had appropriate statistical power to detect differences similar to the previously published literature, the case mix is different with fewer diabetics in our study than one of the large cohort studies used for the calculation [7]. As event rates were higher in the diabetic cohort in this study it may be no effect is shown in our data as a result.…”
Section: Discussionmentioning
confidence: 68%
“…In the previously published case series the rate of dual antiplatelet therapy varied: 31% in a Swedish registry study [7], 55% in a single centre study from America [8] and 69% in an American registry study [9]. The benefits of dual therapy also varied between the studies; with a hazard ratio [HR 0.54] in favour of dual antiplatelet therapy in the Armstrong et al single centre study, HR 0.89 for mortality in the American registry, and HR 0.72 and HR 0.77 for survival and amputation respectively in the Swedish registry.…”
Section: Sample Size Calculationmentioning
confidence: 99%
See 2 more Smart Citations
“…pacientes tratados con angioplastia simple. (70) En los pacientes con isquemia crítica, la progresión hacia gangrena se produce en un 40% de los pacientes diabéticos comparado con el 9% de los pacientes no diabéticos. Es más, la tasa de salvamento de extremidad en pacientes diabéticos con isquemia crítica ha demostrado ser menor que en los pacientes no diabéticos, y la diabetes es un factor de riesgo independiente de amputación y complicaciones postoperatorias en isquemia crítica.…”
Section: Tratamiento No Quirúrgicounclassified